Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12864-018-4544-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical parameters and validation of homopolymer detection in a pyrosequencing-based next generation sequencing system

Abstract: BackgroundCurrent technologies in next-generation sequencing are offering high throughput reads at low costs, but still suffer from various sequencing errors. Although pyro- and ion semiconductor sequencing both have the advantage of delivering long and high quality reads, problems might occur when sequencing homopolymer-containing regions, since the repeating identical bases are going to incorporate during the same synthesis cycle, which leads to uncertainty in base calling. The aim of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“… 30 , 31 While deficient MSH6 immunohistochemical staining would confirm a pathogenic mutation, intact staining would not rule out dMMR because some mutations result in intact expression of dysfunctional protein. 32 - 35 …”
Section: Molecular Tumor Board Discussionmentioning
confidence: 99%
“… 30 , 31 While deficient MSH6 immunohistochemical staining would confirm a pathogenic mutation, intact staining would not rule out dMMR because some mutations result in intact expression of dysfunctional protein. 32 - 35 …”
Section: Molecular Tumor Board Discussionmentioning
confidence: 99%
“…This method is advantageous because it allows for the study of two sequences with high levels of similarity. However, the major drawback of pyrosequencing is that it is not efficient in homopolymeric regions, i.e., genomic sequences that feature the same base sequence but are of different sizes ( 18 , 61 ).…”
Section: Methods For Identifying Polymorphisms In Fcgr mentioning
confidence: 99%
“…The uncertainty is due to the fact that the repeating identical nucleotides have to be incorporated during the same synthesis cycle. Ivády et al (2018) demonstrated that the base calling accuracy suffers greatly as the length of the homopolymer region increases (> identical 4 bases). SomaticSniper Larson et al (2012) is a variant calling tool that applies a homopolymer length filter in order to remove variants that occur in long homopolymer regions as this would mean that they are most probably artifacts due to sequencing errors.…”
Section: Filtering Variants In Homopolymer Regionsmentioning
confidence: 99%